Extreme intelligence development, predicaments, implications - Falck, Sonja (Routledge, 2020)
"In this ambitious and highly original book, Sonja Falck explores the idea that a firm correlation has been demonstrated between higher intelligence and various successful life outcomes and achievements, alongside the contradictory documentation of extremely high intelligence being associated with various poor outcomes. Drawing on the author's own research interviews with the highly gifted, the book argues that understanding the dynamics of how extreme intelligence is cultivated, or hampered, interpersonally can facilitate better outcomes. It will be essential reading for anyone supporting or working with the highly gifted, as well as those researching the field of intelligence"-- Provided by publisher.